Synthesis, Molecular Structure and Quantum Chemical Studies of N-(2 - Hasan Tanak; Karatas, Sadiye; Meral, Seher; Agar, Aysen Alaman (Pleiades Publishing Inc, 2020)
N-(2-Fluorophenyl)-1-(5-nitrothiophen-2-yl)methanimine has been synthesized and characterized by single-crystal X-ray determination. Molecular geometry from X-ray determination of the title compound have been compared using the Hartree-Fock (HF) and density functional theory (B3LYP) method with 6-311++G(d,p) basis set. Calculated results show that density functional theory (DFT) at B3LYP/6-311++G(d,p) level can well reproduce the structure of the title compound. Besides, Mulliken atomic charges, molecular electrostatic potential, and chemical reactivity descriptors (chemical hardess, chemical softness, electronegativity) were also predicted theoretically.